Mental Health Review Board Members’ understanding of the policy guideline on 72-hour assessment - Ontlotlile I. Mpheng; Leepile A. Sehularo; Miriam M. Moagi; Gaotswake P. P. Kovane (Curationis)
Background: The Mental Health Care Act (No 17 of 2002) promotes the involvement of Mental Health Review Board (MHRB) members in the oversight, execution and evaluation of assessments and admissions of individuals in accordance with the 72-h policy guidelines. However, the MHRB experiences dissatisfaction with the implementation of policy guidelines on 72-h assessment of involuntary Mental Health Care Users (MHCUs).